2014
DOI: 10.1111/ggi.12327
|View full text |Cite
|
Sign up to set email alerts
|

In breast cancer, are treatments and survival the same whatever a patient's age? A population‐based study over the period 1998–2009

Abstract: Elderly women compared with the youngest women were diagnosed with more favorable tumor biology (hormone receptor-positive tumors, human epidermal growth factor receptor 2-negative). However, survival was poor in elderly women who had comorbid conditions, did not attend screening mammography examinations and were undertreated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(70 reference statements)
1
7
0
1
Order By: Relevance
“…However, when the mortality from other causes than breast cancer has been taken into account in the relative survival, women aged 70 years or more still have a poorer survival than those less than 70 years. These results are consistent with other studies [12,13]. As breast cancers among elderly women are associated with a more favorable tumor biology, more often being hormone receptor positive and human epidermal growth factor receptor-2 negative compared with younger women, the poorer survival is likely to be due to an inferior treatment.…”
Section: Discussionsupporting
confidence: 92%
“…However, when the mortality from other causes than breast cancer has been taken into account in the relative survival, women aged 70 years or more still have a poorer survival than those less than 70 years. These results are consistent with other studies [12,13]. As breast cancers among elderly women are associated with a more favorable tumor biology, more often being hormone receptor positive and human epidermal growth factor receptor-2 negative compared with younger women, the poorer survival is likely to be due to an inferior treatment.…”
Section: Discussionsupporting
confidence: 92%
“…The age finding is consistent with the literature on the survival of women with breast cancer. Several studies (8,(12)(13) shown a difference in survival among young women and women over 50 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study in France (13) , showed that the relative survival of women aged <50 years was worse than those aged ≥ 50 years). Young women had a greater chance of being associated with a more aggressive tumor, positive lymph nodes and negative hormonal status, which indicates a worse prognosis of the disease (8) .…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant treatment, one of the factors responsible for this trend, is less effective for this stage and age group [ 70 ]. Women older than 70 years also have more comorbidities, and breast-conserving surgery plus adjuvant therapy are used to a lesser extent; both of these factors are related to decreased survival [ 71 ]. In the 85–99 year age group survival increased markedly from 23% in 1985 – 1989 to 62% in 2010 – 2012.…”
Section: Discussionmentioning
confidence: 99%